Assessment of risk factors among cardiovascular patients: A WHO STEPS approach in Bangladesh - Towhid Hasan; Marjia Sultana; Nafisa Habib Purba; Lincon Chandra Shill; Mahmudur Rahman; Md. Asaduzzaman Lashkar; Md. Kamrul Hasan (Acta Scientiarum. Health Sciences, 2023)
Non-communicable diseases (NCDs) have already become the leading cause of death in Bangladesh. Hence, the purpose of the study was to identify the prevalence and determinants of NCDs risk factors among cardiovascular patients in Bangladesh. This cross-sectional study was conducted among 355 cardiovascular patients, aged 18 years and above visiting several tertiary care hospitals in Bangladesh. A validated, structured WHO NCD STEPS questionnaire was utilized to collect information including blood glucose level and lipid profile. Among patients, 58.9% were males and 41.1% females. Tobacco use was observed in 28.7% of the patients and only 1.7% consumed alcohol. Low levels of physical activity were recorded among 44.5% of the participants. Most of the subjects (83.1%) consumed an insufficient amount of fruits and vegetables. The prevalence of overweight and obesity was 41.7% and raised blood pressure was noted among 56.9% of participants. Only 1.7% of respondents were reported to be free from any selected NCDs risk factors. The present study showed a high prevalence of NCDs risk factors among cardiovascular  patients and demands a multisectoral approach by the government and other stakeholders to lessen the impact of NCDs.